Efek Mediasi Perilaku Keuangan Terhadap Hubungan Antara Literasi Keuangan Dengan Keputusan Investasi - Perwito; Nugraha; Sugiyanto (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The results showed that Financial Literacy had a positive effect on Financial Behavior and Financial Behavior mediated in full the influence of Financial Literacy on Investment Decisions. The importance of increasing financial literacy especially for the younger generation / students as agents of change must have good financial attitudes and behavior, the importance of financial knowledge, skills and confidence from an early age, so that in the future they can carry out financial planning and goals, managing consumption, savings and investment, credit, budgeting, and personal income tax management, which can improve the financial well being of his life which will eventually become a stimulus or a stimulus for the progress of economic development. The next hope is that there will be research with increasing complexity both in terms of variables and the scope of the research sample.